THE IMPACT OF KARATE EXTRACURRICULAR ON PARENT SATISFACTION IN ISLAMIC ELEMENTARY SCHOOLS - Indah Nurhidayati; Mujiburrohman; Lu’lu’ Fathimah Nursalma (Universitas Muhammadiyah Surakarta, 2024)
The problems faced by schools related to karate extracurricular education services are students who are less active and easily bored in karate extracurricular activities. This study aims to find out: 1) Karate extracurricular education services at Fatahillah Sukoharjo Integrated Islamic Elementary School, 2) The influence of karate extracurricular education services on the level of parent satisfaction of students of Fatahillah Sukoharjo Integrated Islamic Elementary School. This study uses a quantitative method. The research was conducted at Fatahillah Sukoharjo Integrated Islamic Elementary School. Data collection techniques by documentation and questionnaire/questionnaire methods. The sampling method used a total sampling of 53 respondents. The data were analyzed using a simple linear regression analysis technique with the help of SPSS V25 software. To test the validity of the data, validity tests, reliability tests, normality tests, and linearity tests were carried out. The results of the study show that: 1) Karate extracurricular education services are in the